Effects of Mangosteen pericarp Extract to Clinical Improvements, The Plasma Level of IL-6 and Malondialdehyde in Acute Exacerbation of COPD Patients - Khilyatul Baroroh; Suradi Suradi; Ade Rima (Jurnal Respirologi Indonesia, 2018)
Background: Amplification of inflammation in acute exacerbation of chronic obstructive pulmonary disease (COPD) increases inflammatory mediators and oxidative stress in the airways, pulmonary and systemic circulation that are characterized by increased plasma level of IL-6 and MDA, resulting in worsening of clinical symptoms. Xanthones in mangosteen pericarp have anti-inflammatory and antioxidant effects, potentially as an adjuntive therapy in acute exacerbations of COPD. Methods: The aim of this study was to determine the effect of mangosteen pericarp extract to clinical improvements, plasma level of IL-6 and MDA of acute exacerbation COPD patients. A clinical trial of experimental with pretest and posttest was conducted on 34 acute exacerbation of COPD patients in Dr. Moewardi Hospital Surakarta and Dr. Ario Wirawan Lung Hospital Salatiga from April until May 2016. The sample was taken by consecutive sampling. Subjects were divided by randomized double blind technique into the treatment group (n=17) received mangosteen pericarp extract 2x1100mg/day and control group (n = 17) received placebo. Clinical improvements were measured in CAT score and length of stay. CAT score, plasma level of IL-6 and MDA were measured on admission and at discharge. Length of stay based on the number of days of care in hospitals. Results: There was significant difference (p=0,011) towards decreased of IL-6 plasma level between treatment group (-2,17 ± 3,46 pg/ mL) and control group (+1,67 ± 6,81 pg/mL). There were no significant difference towards decreased of length of stay (p=0,34) between treatment group (4,12 ± 1,54 days) and control group (5,24 ± 2,49 days), towards decreased of CAT score (p=0,252) between treatment group (-19,18 ± 3,96) and control group (-18,24 ± 2,75), and towards decreased of MDA plasma level (p=0,986) between treatment group (+0,03 ± 0,36μmol/L) and control group (+0,35 ± 1,58). Conclusions: The addition of mangosteen pericarp extract 2x1100mg/day during hospitalization was significantly lowered plasma levels of IL-6, but were not significant in lowering the CAT score, shortening the length of stay, and reducing the increase in plasma level of MDA.